Across and within-forest effects on breeding success in Mediterranean Great Tits Parus major - Atiénzar, Francisco; Visser, M. E.; Greño, J. L. (Ardea, 2010)
Forest type and habitat structure can have profound effects on different aspects of avian life histories. These effects may, however, strongly differ across and within forests that vary in vegetation composition and structure, especially when an ancient forest has been replaced by a new forest. To test for these dif- ferences in effect, we studied Great Tit Parus major life-history traits (280 first clutches) in two Mediterranean evergreen forests during 2005–07: an ancient Holm Oak Quercus ilex and a reforested pine forest. A comparison between forests revealed that females breeding in the Holm Oak forest started laying one week later, and produced larger clutches and broods both at hatching and at fledging. Chicks raised in the Holm Oak forest also fledged in better condition. Within forests, however, the reproductive success was not higher for pairs breeding in nestboxes surrounded by oaks within the pine forest, and also re- productive success was not lower in nestboxes surrounded by pines within oak forest. Instead, vegetation maturity around nestboxes, rather than tree species composition, affected hatching success. Surprisingly, hatching success was higher in nestboxes surrounded by immature vegetation. We suggest that this may be due to a lower nest predation rate in nestboxes surrounded by imma- ture vegetation, compared to nestboxes surrounded by mature vegetation. We suggest that different factors appear to affect variation in breeding success in Mediterranean Great Tits comparing across forests (e.g. food availability) vs. within a forest (e.g. nest predation).
Keywords: hatching success; Mediterranean forests; nest predation; Parus major; territory vegetation maturity